Sosialisasi Standar dan Prosedur Keselamatan Pelayaran Wilayah Gugus Kepulauan Sangkarrang Kota Makassar - Andi Chairunnisa Mappangara; Misliah Idrus; Mansyur Hasbullah; Suandar Baso; Abd Haris Djalante; Wihdat Djafar; Andi Mursid Nugraha; Andi Dian Eka Anggriani (Faculty of Engineering UNHAS, 2021)
The safety guarantee for passengers and goods on local inter-island shipping has been overlooked, particularly in the Sangkarrang island group, Makassar City. The following conditions can be seen: the loading process that neglected ship capacity, the position of passengers and goods, fewer safety equipment pieces, the poor state of the pier, and ship worthiness. The government has issued a regulation on traditional shipping safety to protect ship operation activities, such as the requirement of conventional passenger ships, which is regulated the Regulation of the Director-General of Sea Transportation Number HK.103 / 2/8 / DJPL-17 dated 18 April 2017. The program socialization is expected to give awareness of shipping safety for users and operators. This activity's output is the increasing awareness of the community, especially service users and owners of sea transportation fleets who live in the Sangkarrang archipelago, Makassar City. Through this service community program, there will be a higher awareness of the importance of shipping safety. Hence, the operators must prepare minimal safety equipment such as life jackets, buoys, and fire extinguishers on the ship. Besides, service users and ship owners can consider the risk of shipping circumstances.